Political Inequalities Start at Home: Parents, Children, and the Socialization of Civic Infrastructure Online. (3rd April 2018) - Thorson, Kjerstin; Xu, Yu; Edgerly, Stephanie
Abstract : We use a two-wave panel survey of parent-child dyads in the United States to connect online democratic divides with the unequal socialization of political interest in the home. We test a model connecting parent socioeconomic status to the amount of political communication in the home and the subsequent development of youth political interest over the course of an election cycle. We develop the theoretical concept of online civic infrastructure to foreground how interest-driven social media use in adolescence may shape future opportunities for civic and political engagement by building network connections and opening up flows of communication that carry news, political information, and opportunities for mobilization.